The Translation Procedure of Tourism Terms in Garuda Indonesia Inflight Magazine: Colours - Yunita, Annisa Putri; Artawa, Ketut; Qomariana, Yana (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021DO - 10.24843/UJoSSH.2021.v05.i02.p07, 2021)
This study discussed about English-Indonesian articles in Colours Magazine that consists of tourism terms found in the article and translation procedures used by the translator in translating the articles. The data was taken from a magazine entitled Colours. The writer used three English-Indonesian tourism articles of April and December 2019 editions as research objects. The data was collected through library research and used qualitative and descriptive method for data analysis. The theory of translation procedure by Newmark (1988) and Gui Lohmann and tourism terms by Lohman & Netto (2017) were used to analyze the data. The result of this analysis shows that there are 7 types of tourism terms found, those are hospitality, entertainment, recreation, food and beverages, events, landscape, and authenticity in tourism and 7 procedures of translation found in this analysis namely, transference, naturalization, cultural equivalent, descriptive equivalent, reduction & expansion, shift/transposition, and couplets.